2009
DOI: 10.1007/bf03345717
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin assay in wash-out fluid after fine-needle aspiration biopsy in patients with a thyroid nodule and border-line value of the hormone

Abstract: Assaying calcitonin (CT) in the wash-out fluid from fine-needle aspiration biopsies (CT-FNAB) could be useful in the diagnosis of medullary thyroid carcinoma (MTC). The aim of this study was to correlate serum CT with cytology and CT-FNAB. Twenty-seven subjects (age range 27-75 yr) were studied. FNAB was performed in a thyroid nodule (no.=16) or lymph-node (no.=1 previously operated on for MTC) or in the prevalent nodule of multinodular goiters (no.=10). CT-FNAB values obtained in 37 subjects with normal serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 22 publications
(41 reference statements)
1
25
0
1
Order By: Relevance
“…Auto-antibodies against thyroperoxidase (TPOAb) were evaluated by means of the Dia Sorin assay (Saluggia, Italy); concentrations <100 mIU/L were regarded as negative. Serum calcitonin (CT) was assayed by chemiluminescence immunoassay (Dia Sorin); in our laboratory, the upper limit of the normal CT range is <10 ng/L; our institutional cut-off for CT evaluation in needle washing after FNAB is 30 ng/L (Massaro et al, 2009). …”
Section: Patientsmentioning
confidence: 99%
“…Auto-antibodies against thyroperoxidase (TPOAb) were evaluated by means of the Dia Sorin assay (Saluggia, Italy); concentrations <100 mIU/L were regarded as negative. Serum calcitonin (CT) was assayed by chemiluminescence immunoassay (Dia Sorin); in our laboratory, the upper limit of the normal CT range is <10 ng/L; our institutional cut-off for CT evaluation in needle washing after FNAB is 30 ng/L (Massaro et al, 2009). …”
Section: Patientsmentioning
confidence: 99%
“…This method, previously employed for the early detection of cervical metastases following thyroidectomy and radioiodine therapy, allows an early diagnosis of lymph node metastases before surgery and is mostly employed in cases with small thyroid nodules but with enlarged lymph nodes that are highly suggestive of malignancy (52,53,54). Assessment of calcitonin level in the washout fluid from FNAB of cervical lymph nodes can also be used as a potentially highly reliable diagnostic procedure to identify primary and recurrent/metastatic MTC (52,54,55).…”
Section: Introductionmentioning
confidence: 99%
“…C cells produce calcitonin and the measurement of calcitonin in needle washout after biopsy is helpful in localizing MTC. The few articles that evaluated the role of FNA‐calcitonin for the diagnosis of MTC consistently showed that FNA‐calcitonin has a high accuracy …”
Section: Methodsmentioning
confidence: 99%